The Optimal Oil-Saving Pathway Until 2030 for China Road Passenger Transportation Based on a Cost Optimisation Model - Z. Li; J. Liang; P. Liu; L. Ma (Chemical Engineering Transactions, 2015)
Optimal planning of oil-saving pathway for road passenger transportation sector remains a challenging task, as it involves many powertrains and fuel alternatives in the course of traffic volume expansion. This manuscript proposed a cost-optimisation superstructure model (COSM) to derive the optimal oil-saving pathway for road passenger transportation up to 2030. In each year of the planning horizon, the model considered eight options of alternative fuels and powertrains for seven categories of newly registered passenger vehicles which was derived from the projected vehicle population and survival rates. The optimisation objective of the model was to minimize the accumulated costs of fuels and vehicles over the planning horizon, and the optimal oil saving pathway was then decided by choosing the most cost-effective options of alternative fuels and powertrains for annual newly registered vehicles from 2010 to 2030. Based on the COSM, the empirical study of China indicated that the cost-optimal oil saving potential was 61 and 126 Mt (OE) in 2020 and 2030. The sensitivity analysis indicated that supply amount of vehicular natural gas was more sensitivity than that of vehicular gasoline, gasoline price was more sensitivity than natural gas price, and acquisition cost of PEV (pure electricity vehicle) was more sensitive than that of HFCV (hydrogen fuel cell vehicle).